Early anglicism in the 19th Peru century - Arrizabalaga Lizárraga, Carlos (2016)
The article focuses on the early Anglicisms imposed on many Hispanic dialects due to the greatpower of the British Commercial Imperialism all through the 19th century, which are completelyadapted to the Spanish phonetics and morphology, and thus transcribed with the Spanish spelling.These are words that do not seem to be Anglicisms since they have been completely assimilated,such as “chompa” (from “jumper”), “saco” and “chaqueta” (from “jacket”), “lonche” (from“lunch”), “faite” (from “fighter”), “queque” (from “cake”) and “gasfitero” (from “gasfiter”). Thecase of “lonche” is particularly mentioned regarding its lexicographical use. In addition, the articlepoints out the existence of some phraseology taken from English, and also of some Peruvianexpressions used in the English language spoken in the south west of the United States.